2019
DOI: 10.1590/s1517-707620190001.0649
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Al-Y Coating on γ-TiAl at 900°C

Abstract: In this study, an Al-Y coating was applied to enhance the property of oxidation resistance on the surface of γ-TiAl alloys by rf magnetron sputtering. The isothermal oxidation tests were investigated at 900 °C for 100 h. The coating characteristics and microstructure of coating after isothermal oxidation were inspected by XRD and SEM methods respectively, and coating bonding strength was investigated by scratch tester. Results show that Al 2 O 3 and Y 2 O 3 were produced on the surface of γ-TiAl alloys to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 31 publications
5
47
1
Order By: Relevance
“…In fungal pathogens, polarized growth depends on a specialized protein subcomplex called polarisome (Harris et al, 2005). The accurate localization of Spa2, a central component of polarisome, is required for establishment of proper hyphae polarized growth in filamentous fungal pathogens (Meyer et al, 2008;Li et al, 2014;Cao et al, 2021;Zheng et al, 2021b;Zhu et al, 2022). In this study, approximate 40% of the vegetative hyphae of the MoMih1 showed abnormally swollen tips, and the central localization of MoSpa2-eGFP observed in the polarisome of KU80 was completely abolished in the swollen hyphae tips or asymmetrically localized in the twisted hyphae tips of MoMih1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…In fungal pathogens, polarized growth depends on a specialized protein subcomplex called polarisome (Harris et al, 2005). The accurate localization of Spa2, a central component of polarisome, is required for establishment of proper hyphae polarized growth in filamentous fungal pathogens (Meyer et al, 2008;Li et al, 2014;Cao et al, 2021;Zheng et al, 2021b;Zhu et al, 2022). In this study, approximate 40% of the vegetative hyphae of the MoMih1 showed abnormally swollen tips, and the central localization of MoSpa2-eGFP observed in the polarisome of KU80 was completely abolished in the swollen hyphae tips or asymmetrically localized in the twisted hyphae tips of MoMih1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature on NiO x and WO x degradation, such a decrease is likely related to the irreversible trapping of the intercalated ions, possibly associated with the microstructural or pore-size change at the coating surface after thousands of cycles. 45,46 For irreversible ion trapping, quantifications at 0.01 atom % precision would be needed for measuring the concentration change of the intercalated species and will be done in a future study.…”
Section: Bipolar Electrochromic Reactionsmentioning
confidence: 99%
“…Therefore, accurate longan fruit detection is the difficult part of realizing automatic yield estimation, which directly affects the accuracy and efficiency of orchard yield estimation. In recent years, researchers in related fields have used shape matching, color space transformation, threshold segmentation, multiscale feature fusion, fuzzy clustering and other methods to identify, detect and classify apples, oranges and other fruits (Jaisin et al, 2013;Xiong et al, 2018;Zhuang et al, 2019;He et al, 2020;Lin et al, 2020). The traditional machine learning methods used in these studies can only be used for image processing tasks with simple background conditions, and have poor robustness in the face of very complex actual orchard scenes.…”
Section: Introductionmentioning
confidence: 99%